2020
DOI: 10.1212/nxg.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk for Alzheimer disease predicts hippocampal volume through the human lifespan

Abstract: ObjectiveTo test the hypothesis that genetic risk for Alzheimer disease (AD) may represent a stable influence on the brain from early in life, rather than being primarily age dependent, we investigated in a lifespan sample of 1,181 persons with a total of 2,690 brain scans, whether higher polygenic risk score (PGS) for AD and presence of APOE ε4 was associated with lower hippocampal volumes to begin with, as an offset effect, or possibly faster decline in older age.MethodsUsing general additive mixed models, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 41 publications
3
35
1
Order By: Relevance
“…An exception is Elliott and colleagues 3 , who found that middle-aged individuals with higher brain age already exhibited poorer cognitive function and brain health at age three years. This fits a robust corpus of literature showing effects of lifelong, stable influences as indexed by childhood IQ 14 , genetics 10 , and neonatal characteristics 8 on brain and cognitive variation in old age.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…An exception is Elliott and colleagues 3 , who found that middle-aged individuals with higher brain age already exhibited poorer cognitive function and brain health at age three years. This fits a robust corpus of literature showing effects of lifelong, stable influences as indexed by childhood IQ 14 , genetics 10 , and neonatal characteristics 8 on brain and cognitive variation in old age.…”
Section: Discussionsupporting
confidence: 79%
“…If brain age reflects accelerated brain aging, cross-sectional brain age delta - indexed by the centercept - should be positively associated with yearly increases of brain age delta over time (brain age delta long ) . If the early-life account plays a substantial role, one should observe a relationship between brain age and early factors - indexed here as birth weight and polygenic scores for brain age (PGS-BA) given evidence of lifelong effects of genetic risk on age-related phenotypes 9,10 ( Fig. 1b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observe an age-dependent decrease in the volume of structures such as the thalamus, caudate and accumbens in UK Biobank participants agreeing with the variable neurodegeneration hypothesis. Walhovd et al 41 examined the association between AD PRS and hippocampal volume in 1,181 cognitively healthy people with a wide age range (4–95 years). They identified an effect of a higher AD PRS on reduced hippocampal volumes in a sample of young adults, which was consistent across age groups.…”
Section: Discussionmentioning
confidence: 99%
“…How and when these risk loci mediate pathogenesis of AD is a broad question and active area of research. Walhovd et al 7 studied the relationship between increased polygenic risk in AD and structural brain measures decades before the predicted development of neurodegenerative disease. The group analyzed hippocampal volume by brain MRI from 1,181 cognitively normal individuals aged 4–96 years.…”
mentioning
confidence: 99%